2006
DOI: 10.1094/phyto-96-0356
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Citrus Viroids Affect Symptom Expression and Field Performance of Clementine Trees Grafted on Trifoliate Orange

Abstract: Citrus exocortis viroid (CEVd), Citrus bent leaf viroid (CBLVd), a noncachexia variant of Hop stunt viroid (HSVd), Citrus viroid III (CVd-III), and Citrus viroid IV (CVd-IV) were co-inoculated as two-, three-, four-, and five-viroid mixtures to Clementine trees grafted on trifoliate orange to evaluate their effect on symptom expression, tree growth, and fruit yield. Most trees infected with CEVd-containing viroid mixtures developed exocortis scaling symptoms, as did CEVd alone, whereas most trees infected with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 33 publications
4
56
0
5
Order By: Relevance
“…The host range study reported here illustrates that, like other citrus viroids, CVd-V can infect all the citrus species and cultivars tested. The phenotypic alterations incited by CVd-V infection on commercial species and cultivars are not known, but the synergistic effects described in Etrog citron co-infected with CVd-V and CBLVd or CDVd suggest that similar interactions may result in reduced tree size and yield, as reported for clementine trees grafted on trifoliate orange (Poncirus trifoliata L.) co-infected with several viroids (Vernière et al 2006). …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The host range study reported here illustrates that, like other citrus viroids, CVd-V can infect all the citrus species and cultivars tested. The phenotypic alterations incited by CVd-V infection on commercial species and cultivars are not known, but the synergistic effects described in Etrog citron co-infected with CVd-V and CBLVd or CDVd suggest that similar interactions may result in reduced tree size and yield, as reported for clementine trees grafted on trifoliate orange (Poncirus trifoliata L.) co-infected with several viroids (Vernière et al 2006). …”
Section: Resultsmentioning
confidence: 97%
“…When a plant infected with a latent or mild strain of a viroid becomes protected against subsequent infection with a severe strain of the same viroid, the typical symptoms of the second strain and its accumulation level is abolished or attenuated, a phenomenon known as "cross-protection" (Pallas and Flores, 1989;. Conversely, co-inoculation with two unrelated viroids may result in a synergistic interaction, with symptoms being more severe that those expected for purely additive effects of the two viroids (Vernière et al 2006. Given the high sequence identity between Ch5 and CVd-V, Ch5 could be regarded as a latent strain of CVd-V and a "cross-protection" phenomenon should be expected in coinfected plants.…”
Section: Discussionmentioning
confidence: 99%
“…The phenotypic alterations incited by CVd-V infection on commercial species and cultivars are not known, but the synergistic effects described in Etrog citron coinfected with CVd-V and CBLVd or CDVd (20) suggest that similar interactions may result in reduced tree size and yield, as reported for clementine trees grafted on trifoliate orange (Poncirus trifoliata L.) coinfected with several viroids (24).…”
Section: Discussionmentioning
confidence: 99%
“…Since bark-cracking symptoms in Tahiti lime are not infrequent in Colombia, viroid infections could be the cause ). In addition, CEVd infection of trees also co-infected with HSVd and CDVd may produce undesirable effects, such as those reported by Vernière et al, (2004Vernière et al, ( , 2006 in the case of trees grafted on the viroid-sensitive trifoliate orange. One of the viroid infected Tahiti lime sources from Magdalena municipality (Tahiti lime 6) was obtained from a tree grafted on Carrizo citrange, which is also viroid-sensitive, and therefore such trees may suffer from the sensitivity of both scion and rootstock.…”
Section: Discussionmentioning
confidence: 99%